Where, When, and How: Are they all sensorimotor? Towards a unified view of the dorsal pathway in vision and audition. (January 2018) - Rauschecker, Josef P.
Abstract: Dual processing streams in sensory systems have been postulated for a long time. Much experimental evidence has been accumulated from behavioral, neuropsychological, electrophysiological, neuroanatomical and neuroimaging work supporting the existence of largely segregated cortical pathways in both vision and audition. More recently, debate has returned to the question of overlap between these pathways and whether there aren't really more than two processing streams. The present piece defends the dual-system view. Focusing on the functions of the dorsal stream in the auditory and language system I try to reconcile the various models of Where, How and When into one coherent concept of sensorimotor integration. This framework incorporates principles of internal models in feedback control systems and is applicable to the visual system as well.